More than costs: On the fit between solar and renewable electricity policy motivations and energy system models - Lilliestam, Johan; Blumer, Yann; Geddes, Anna; Labordena, Mercè; Späth, Leonhard; Van Vliet, Oscar (Solar power : technologies, environmental impacts and future prospects, 2014)
Solar and other renewable power can play an important role in the future European electricity system, as shown by numerous energy and electricity system model studies. Many of these reports have in common that they focus on cost as the central issue, either by optimizing it or using it as a key variable in simulation. In this paper, we examine the renewable energy policies in Germany, the Netherlands, Spain, Switzerland and the UK in order to identify the policy motivations and constraints for expanding renewables in these countries, in order to find out whether this cost-focus reflects actual policy priorities. We find that their renewable energy policies are motivated by climate concerns and international agreements, energy security concerns, as well as job creation, and other macroeconomic or industry policy reasons. They are constrained primarily by short-term costs of renewable electricity support and grid integration challenges. Thus, actual policies are not very concerned with overall system costs and yet this is the issue many researchers focus on in their scenario building. We contend that the political and scientific debates, including scientific system modelling, on deployment of renewable electricity should go beyond mere cost optimisation studies and focus instead on issues that actually drive and constrain policies today.
CRIS-Team Scopus Importer:2023-06-14